Comparison of Histomorphometric Study of Chromaffin Cells in Adult Males Squirrel (Sciurusanomalus) and Hamster (Mesocricetusauratus) - kadhim, Abdulrazzaq B; Khaleel, Iman M (The Iraqi Journal of Veterinary Medicine, 2021)
The adrenal glands are endocrine glands that produce a diversity of hormones comprising of adrenaline, the aldosterone and cortisol. The present study aimed at investigation of the histomorphometric features of chromaffin cells. There were two types of chromaffin cells. In squirrel, the first type was columnar in shape and brownish in color contained spherical nucleus located at the base of cells, which represented the epinephrine secreting cells, and the second type was polygonal in shape and light brownish in color contained spherical nucleus located in the center of cells, which represented the norepinephrine secreting cells. The adrenal medulla of hamster consists almost entirely of columnar or polyhedral chromaffin cells forming clusters and anastomosing cords separated by sinusoids, giving a strong reaction with methylene eosin stain more than that seen in squirrel. The statistical analysis showed that the means diameter of epinephrine cells and norepinephrine cells in the right adrenal gland in squirrel were lesser than those of hamster significantly at P<0.05, but in the left adrenal gland in squirrel the means were greater than those of hamster significantly at P<0.05. In conclusion, the present findings showed the reaction of chromaffin cells of hamster with methylene –eosin stain to be stronger than with hematoxylin-eosin stain, while the opposite was true in case of the squirrel.